2002
DOI: 10.1038/sj.bjp.0704624
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Ca2+ influx through ATP receptors on rat brain synaptosomes: identification of functional P2X7 receptor subtypes

Abstract: 1 ATP receptors of the P2X class have previously been identi®ed on autonomic nerve endings and on a limited population of CNS neurons. 2 In the present study P2X receptors on mammalian cortical synaptosomes have been identi®ed by a variety of functional and biochemical studies. In choline bu er ATP analogues caused concentration/time dependent Ca 2+ in¯ux. Relative to the e ects caused by ATP, benzoylbenzoyl ATP (BzATP) was about seven times more active than ATP while 2-me-S-ATP and ATPgS were much less active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 71 publications
3
31
0
Order By: Relevance
“…Recent functional studies, in combination with immunolocalization using the same Abs we used in this study, have concluded that presynaptic P2X 7 receptors in the hippocampus may modulate synaptic transmission at these sites (Armstrong et al, 2002;Lundy et al, 2002;Sperlagh et al, 2002;Atkinson et al, 2004;Cavaliere et al, 2004). However, extracellular ATP activates not only ionotropic P2X receptors but also metabotropic P2Y receptors and, because it is readily broken down to adenosine, adenosine receptors.…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…Recent functional studies, in combination with immunolocalization using the same Abs we used in this study, have concluded that presynaptic P2X 7 receptors in the hippocampus may modulate synaptic transmission at these sites (Armstrong et al, 2002;Lundy et al, 2002;Sperlagh et al, 2002;Atkinson et al, 2004;Cavaliere et al, 2004). However, extracellular ATP activates not only ionotropic P2X receptors but also metabotropic P2Y receptors and, because it is readily broken down to adenosine, adenosine receptors.…”
Section: Discussionmentioning
confidence: 57%
“…1 A). These Abs have been used in previously published reports examining P2X 7 receptor localization and function in neuronal and nonneuronal tissues (Worthington et al, 1999a,b;Deuchars et al, 2001;Kim et al, 2001;Sluyter et al, 2001;Armstrong et al, 2002;Atkinson et al, 2002Atkinson et al, , 2004Le Feuve et al, 2002;Lundy et al, 2002;Sperlagh et al, 2002;Ishii et al, 2003). We found that Cterm-Ab, but not ectoAb-1 or ectoAb-2, were highly selective for P2X 7 receptor protein when expressed in HEK293 cells and compared with untransfected (Fig.…”
Section: Wild-type Rat and Mouse Brainmentioning
confidence: 56%
See 3 more Smart Citations